2000
DOI: 10.1098/rspb.2000.1092
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of sea bass populations in the western and eastern Mediterranean as revealed by microsatellite polymorphism

Abstract: We studied the genetic structure at six microsatellite loci of the Mediterranean sea bass (Dicentrarchus labrax) on 19 samples collected from di¡erent localities in the western and eastern Mediterranean basins. Signi¢cant divergence was found between the two basins. The distance tree showed two separate clusters of populations which matched well with geography, with the noticeable exception of one Egyptian sample which grouped within the western clade, a fact attributable to the introduction of aquaculture bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
149
1
15

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(184 citation statements)
references
References 43 publications
19
149
1
15
Order By: Relevance
“…F ST values indicated that the highest differentiation was observed between eastern (Turkish) and western populations and differentiation was higher when comparing western samples with Marmara Sea (mean F ST  = 0.3) than with Aegean Sea (mean F ST  = 0.22). Such deep genetic break between eastern and western Mediterranean populations has been reported in various species such as fish, molluscs, or the seagrass Posidonia oceanica (Arnaud‐Haond et al., 2007; Bahri‐Sfar, Lemaire, Hassine, & Bonhomme, 2000; Nikula & Väinölä, 2003). An east–west divergence has been observed for the octocoral P. clavata but with only one sample in the eastern basin (Mokhtar‐Jamaï et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…F ST values indicated that the highest differentiation was observed between eastern (Turkish) and western populations and differentiation was higher when comparing western samples with Marmara Sea (mean F ST  = 0.3) than with Aegean Sea (mean F ST  = 0.22). Such deep genetic break between eastern and western Mediterranean populations has been reported in various species such as fish, molluscs, or the seagrass Posidonia oceanica (Arnaud‐Haond et al., 2007; Bahri‐Sfar, Lemaire, Hassine, & Bonhomme, 2000; Nikula & Väinölä, 2003). An east–west divergence has been observed for the octocoral P. clavata but with only one sample in the eastern basin (Mokhtar‐Jamaï et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic segregation of Mediterranean and Atlantic stocks might occur as a result of both the Straits of Gibraltar and the Almeria-Oran oceanographic front (in the western Mediterranean) acting as barriers to dispersal. This is likely the case in a number of species of both fish and cephalopods (Lundy et al 1999, Naciri et al 1999, Bahri-Sfar et al 2000, Dillane 2001. Conversely, there is evidence to suggest that movement between the Mediterranean and Atlantic occurs in some species of finfish and shellfish, such as swordfish (Kotoulas et al 1995), the European anchovy (Magoulas et al 1996) and lobsters (Stamatis et al 2004).…”
Section: Genetic Differentiation Within European Watersmentioning
confidence: 96%
“…Genetic analyses of these two gobiine species have revealed a population subdivision which has clearly demonstrated the action of the STS as breakpoint to gene flow within the Gobidae family. Such genetic differentiation has been also observed in several marine species like the flounder (Platichthys flesus; Borsa et al, 1997), the sea bass (Dicentrarchus labrax; Bahri-Sfar et al, 2000), the mackerel (Scomber japonicus, Zardoya et al, 2004), the bottlenose dolphins (Tursiops truncates; Natoli et al, 2005) and the carmote prawn (Penaeus kerathurus, Zitari-Chatti et al, 2009). Given the different taxonomic groups involved and the different degree of differentiation within these species, the contribution of the STS extends to more than the mere function of a simple barrier promoting intra-specific genetic differentiation.…”
Section: West Vs East Mediterranean Splitmentioning
confidence: 98%
“…Characterized by a series of 'quasi-permanent features', such as vortices and crests (Hamad et al, 2006), such a hydrographic regime bounds the natural dispersal across the STS. This, therefore, permits a progressive genetic differentiation within several species and exerts a strong influence on the mechanisms that counteract gene flow and promote structuring in the Mediterranean ecosystem (Bahri-Sfar et al, 2000;Perez-Losada et al, 2007). The split into W-MED and E-MED P. marmoratus clades matches rather well that observed in the sand goby P. minutus (Stefanni & Thorley 2003) and in the tortonese goby P. tortonesei (Mejri et al, 2009).…”
Section: West Vs East Mediterranean Splitmentioning
confidence: 99%
See 1 more Smart Citation